Towards biohythane production from biomass: Influence of operational stage on anaerobic fermentation and microbial community. (23rd February 2016) - Si, Buchun; Liu, Zhidan; Zhang, Yuanhui; Li, Jiaming; Shen, Ruixia; Zhu, Zhangbing; Xing, Xinhui
Abstract: Biohythane consisting of biohydrogen and biomethane via two-stage fermentation is a promising energy carrier for vehicle use. In this study, one-stage biomethane system using upflow anaerobic sludge blanket (UASB) and packed bed reactor (PBR) was shifted to the two-stage biohythane system to study the influence of operational stage. Compared with biomethane system, the biohythane process achieved higher COD removal and energy recovery. Particularly, the total COD removal in the PBR system rose significantly from 74.0 to 97.3%, corresponding to an increased energy recovery from 54.2 to 67.1%. The first-stage hydrogen fermentation had a positive effect on subsequent biomethane production in biohythane system. The analysis of microbial diversity using Illumina MiSeq sequencing showed significant changes of microorganisms in biomethane reactor, which revealed the variation of biochemical pathways. Compared to biomethane system, the relative abundance of acidogenesis bacteria was reduced in biohythane system, such as family Clostridiaceae . By contrast, the amount of acetogens ( Syntrophaceae, Syntrophomonadaceae and Desulfovibrionaceae ) and acetate-oxidizing bacteria ( Spirochaetes ) was increased. The archaea community remained stable, and mainly consisted of acetoclastic methanogens from family Methanosaetaceae . These results indicated the biomethane reactors in biohythane system had more efficient acidogenesis and acetate-utilizing microbial community. Graphical abstract: Highlights: Study the effect of operational stage on anaerobic fermentation using UASB and PBR. Higher COD removal and energy recovery were achieved in biohythane system. Illumina MiSeq sequencing showed notable microbial changes in methane reactors. Enhanced acetogenesis and acetate-oxidizing in methane reactor in biohythane system.